SIFAT HIPOGLIKEMIK DAN HIPOKOLESTEROLEMIK PROTEIN KEDELAI PADA TIKUS MODEL TOLERANSI GLUKOSA TERGANGGU (TGT) INDUKSI ALLOKSAN 1) [Hypoglycemic and Hypocholesterolemic Activities of Soy Protein on Impared Glucose Intolerant Rats Induced by Alloxan] - Masun Lasimo; Zuheid Noor; Y. Marsono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Previous studies indicated that soy protein had hypoglycemic and hypocholesterolemic activity in induced diabetic rats. However when combined with different sources of carbohydrate, the effects were not known yet. The purpose of this research was to evaluate the hypogylcemic and hypocholesterolemic properties of soy protein combined with cornstarch or wheat flour, on four groups of impaired glucose tolerance (IGT) alloxan induced male Wistar rats models. During the first two weeks, rats were given high fat and cholesterol diet to induce hypercholesterolemic. On the third week, rats were injected with alloxan 60 mg/kg body weight to induce hyperglycemia, and in the following three weeks each group was given one of the following, casein+cornstach (CC), soy protein+cornstarch (SC), casein+wheat flour (CW), or soy protein +wheat flour (SW). The glucose and lipid concentrations of blood of individual rat were measured before and, 1st , 7th, 14th, and 21th day after the injection of alloxan.The results showed that the soy protein diets have hypoglycemic and hypocholestrolemic activity as compared to casein diets. The different source of carbohydrate diet affected hypocholesterolemic property of soy protein, but did not affect hypoglycemic property. It seems that the SC diet decreases glucose concentration more than the SW diet (17,45% and 7,04% from baseline, respectively). The SC diet had more ability to decrease total and LDL cholesterol (9,52% and 21, 89% from baseline, respectively), while the SW diet had more ability to decrease triglycerides (24,64% from baseline).